Działalność wydawnicza i publikacje Towarzystwa im. Michajła Kaczkowskiego w latach 1875–1885 – ujęcie ogólne - Sedliar, Oleksandr (Biblioteka Uniwersytecka w Poznaniu, 2018)
W niniejszym tekście charakteryzuję skrótowo działalność wydawniczą oraz publikacje (książki niewielkich rozmiarów i objętości, publikowane z comiesięczną częstotliwością) ukraińskiego Towarzystwa im. Michajła Kaczkowskiego w okresie pierwszych 10 lat jego funkcjonowania. Było to stowarzyszenie rusofilskie, działało w Galicji Wschodniej i realizowało zadania oświatowe na rzecz miejscowych Ukraińców (Rusinów), zarówno ze środowisk miejskich, jak i wiejskich. Główną formę wykonawczą stanowiło wydawanie i rozpowszechnianie broszur o nastawieniu popularyzatorskim. Autorami byli przeważnie amatorzy, ale tematyka była rozległa. Wkraczała w różne obszary wiedzy – w ujęciu popularnym i z zachętą do czytania. W początkach lat 80. XIX wieku zaostrzyła się na tych obszarach walka polityczna. Władze regionalne zaczęły silniej przeciwdziałać przedsięwzięciom rusofilskim, co miało wpływ również na stosowne wyprofilowanie edytorskiej działalności Towarzystwa. Znaczenie miał także wzrost środowiskowej aktywności społecznej oraz istotne powiększenie się publiczności czytającej. Nie bez wpływu pozostawała też oferta konkurencyjna ze strony innych organizacji oświatowych – ukraińskich oraz polskich.

The present article briefly discusses the publishing activity and publications (small size books published on a regular monthly basis) of the Ukrainian Michal Kachkovsky Society within the first ten years of its existence. The society, explicitly engaged in the Ukrainian national interests and Russophile position, was operating in Eastern Galicia (Eastern Poland) and was engaged in educational work and supportive activities in the interest of the local Ukrainians (Ruthenians) from both city and rural environments. The main executive form of the society was to publish and promulgate popular brochures widely in accordance with the pursued agenda by the society. The authors of the brochures were mostly amateurs, thought the subjects raised were many and varied. The subjects included a number of different areas of knowledge, popularised subject themes and encouraged further reading. At the beginning of the 1880s, domestic political struggle became inextricably connected with the political friction in the region. Regional authorities started to oppose more and more strongly any pro-Russian undertakings, which, accordingly, had its impact on the profile of the editorial activity of the Society. Yet another important factor enhancing the effects of the change in the attitude was the increase in the social activity of the population and the following significant increase in the number of readers. In addition, the offer proposed from other competitive educational organisations, both Polish and Ukrainian, had its own share in the resulting situation.
Publishing activity and publications of the Michal Kachkovsky Society in the years 1875–1885: a general approach
Keywords: działalność oświatowa w XIX wieku; ukraiński ruch wydawniczy; Galicja Wschodnia; popularna literatura „dla ludu”; rusofilstwo w Galicji Wschodniej; Towarzystwo im. Mychajła Kaczkowskiego; educational activity in the 19th c.; Ukrainian publishing movement; Eastern Galicia; popular literature; Russophilism in Eastern Galicia; Michal Kachkovsky Society